Peran Diferensiasi Produk Mobil Nissan Terhadap Minat Beli Konsumen pada PT. Wahana Rejeki Mobilindo Cirebon Cabang Indramayu - Agus Yudianto; Meddy Nurpratama (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The technological development of the Indonesian people has brought about major changes in both the infrastructure that supports the lives of the Indonesian people and the quality of life of the people themselves. Expressways as a land transportation infrastructure for the people of Indonesia have undergone rapid development as evidenced by the emergence of various expressways connecting one city to another. Wheeled vehicles or cars as means of transportation have played an important role in society. The state of the Indonesian auto industry itself is currently very active, with many new players in the sector, so automakers are expected to face more competition, especially with the entry of auto products from South Korea. are forced to market. Around 1996-1997, they sold cars of the same class as Japanese and European cars. Analytical Methods Two analytical methods are used in this study, namely (1) descriptive and (2) descriptive, according to the problem formulation, research objectives, hypothesis formulation, and the nature of the data collected. A method of linear regression analysis. The correlation (r) between the two variables product differentiation and consumer intent using multiple correlation is 0.740, indicating a strong estimate between product differentiation and consumer intent. Based on the results, the coefficient value is 54.76%. This means that the product differentiation of Nissan cars can explain the consumer's 54.76% of his purchase intentions, while the remaining 45.24% are influenced by other factors that have not been studied. B. Intense competition for similar products, differences in consumer tastes, low customer loyalty, etc.